Development of Chaoshan Folk Songs Piano Teaching Guidebook For Freshmen Students - Shang, Rui; Phokha, Pramote (Journal of Ecohumanism, 2025)
This research aims to explore the historical and cultural background, as well as the musical characteristics of Chaoshan folk songs, and to use this knowledge to develop a piano teaching guidebook. Chaoshan folk songs, originating from the Chaoshan region of Guangdong Province in China, are an important part of the region’s cultural heritage. They are known for their distinctive melodies, expressive lyrics, and unique performance styles. The first objective of the research is to delve into the historical roots and cultural significance of these songs, identifying key musical elements that define their structure and sound. Building on this foundation, the second objective is to develop a piano teaching guidebook tailored specifically for instructing Chaoshan folk songs. This guidebook will provide a systematic approach to teaching these songs, incorporating traditional techniques and modern pedagogical methods. Finally, the third objective is to implement the guidebook in a classroom setting and evaluate its effectiveness. By conducting a teaching experiment, this research will assess how well the guidebook enhances students' understanding and performance of Chaoshan folk songs on the piano. The evaluation will focus on student progress, engagement, and overall satisfaction with the learning experience. This research seeks to contribute to preserving and promoting Chaoshan musical traditions while providing a valuable educational resource for piano instructors.